the The Impact of the Transition in Ethiopia on Geopolitical Dynamics in the Horn of Africa post-2018 - Yadano Hundera Dube (Indonesia Prime, 2022)
Abstract The Horn of Africa is the most militarized and conflict-ridden region on the African continent. For many decades, armed conflicts have raged within states, between states, and among proxies. For a long period of time, Ethiopia has been playing a key role in stabilizing the peace and security of the region. In January 2018, the EPRDF declared that it would pursue reforms in response to the intensifying of youth-led antigovernment protests that began in November 2015, leading to reforms in the party that brought Abiy Ahmed to become Prime Minister. This paper focuses on evaluating the impact of internal dynamics in Ethiopia post-transition on the geopolitics of the Horn. The essay was written mainly based on a review of related literature. Recently, the country has been deeply embroiled in political and socio-economic crises. In particular, the war in the northern part of the country has ravaged the country and harmed its foreign relations. Ethiopia has yet to fully leverage its vast material and human resources to advance its key role in the region and the continent. Enhancing internal unity through inclusive dialogue should be given top priority to preserve and extend the regional role of Ethiopia in the region.